Inclusive Excellence: A new University Model in the 21st Century Based on Universal Design for Learning - L.M. Volosnikova; L.V. Fedina (Moscow State University of Psychology and Education, 2023)
Affordable high-quality university education is a moral and legal imperative today. At the same time, there are still numerous barriers to get this university education. The orientation of higher education towards world rankings and economic efficiency indicators contradicts with inclusive values and goals. Inclusive politics needs radical revision and updating. The aim of this research is to design an inclusive university model based on universal educational design. The research method is a review and theoretical analysis of scientific publications devoted to inclusive higher education and published on the platforms SpringerLink, PubMed, Frontiers and Taylor & Francis Group. The paper examines the concepts of inclusive excellence and universal design for learning and provides a theoretical analysis of the possibility of using these approaches to transform a modern university. The authors propose a model that takes into account: organizational culture, indicators of inclusive excellence, principles of transformation of the educational environment, external factors, global and national context and the process of transformation (involvement, representation, action through a plurality of means and environments based on agency). The expected result is of high importance for Russian and world science and is in the trend of key scientific research of education and its transformation, focused on the values of social justice, accessibility and equal opportunities, and also responds to the crisis situation in the humanities.